Between Nationalism, Internationalism and Colonial Quadrillage: The Action Chrétienne en Orient in Mandatory Syria (1922–1946). (January 2022) - Bourmaud, Philippe
Despite growing internationalization, national ties have remained a structural aspect of missionary and humanitarian work. This was especially true of the Interwar period in the Middle East, where colonial powers, independent states and political ideologies competed. The beginnings of the Action Chrétienne en Orient (ACO) bear witness to this: the ACO, specialized in assistance to Christian Anatolian refugees and missionary work towards Muslims, made strategic use of its national connections. It retained German and Protestant connections, while serving as a formally French broker between refugees or Protestant missionary organizations and the French colonial authority. Yet as looming independence seemed to threaten the position of Christian refugees, the ACO gradually entered the 'colonial quadrillage' through which France exerted guidance over voluntary organizations.